2004
DOI: 10.1021/jp049230g
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Ternary Oxide Nanowires by Gold-Catalyzed Vapor-Phase Evaporation

Abstract: Zn2SnO4 nanowires and Zn2SnO4 diameter-modulated (DM) nanowires were successfully synthesized, accompanied by the formation of ZnO nanowires, via the thermal evaporation of a mixture of ZnO and SnO2 powders, using gold as a catalyst. Their morphologies and structures were characterized by scanning electron microscopy, X-ray spectroscopy, and high-resolution transmission electron microscopy. The ZnO nanowires were single crystalline, with an axis of [011̄0], which is different from the conventional [0001] orien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
67
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 28 publications
3
67
1
Order By: Relevance
“…The After hydroxyl anions are generated, they immediately precipitate in presence of Zn 2+ to form Zn(OH) 2 which is easily dehydrated above 65…”
mentioning
confidence: 99%
“…The After hydroxyl anions are generated, they immediately precipitate in presence of Zn 2+ to form Zn(OH) 2 which is easily dehydrated above 65…”
mentioning
confidence: 99%
“…[4][5][6][7] Zn 2 SnO 4 is normally synthesized by solid state reactions with ZnO and SnO 2 at high temperatures. 8,9 The high temperature calcination of coprecipitated Zn and Sn hydroxides with the alkali from an aqueous solution were also used to prepare Zn 2 SnO 4 . 4,10 Recently, the hydrothermal synthesis of Zn 2 SnO 4 was reported.…”
mentioning
confidence: 99%
“…The results indicated that MB dye of 10 mg/l was photolyzed up to 5% in 2 hr. This degradation efficiency was negligible when the different sized (24,35 and 53 nm) nanoparticles were added to the solution under illumination. When there was no UV light, the concentration of MB dye with the addition of ZTO photocatalysts remains unchanged for 2 hr.…”
Section: Photocatalytic Performance Of Zto With Mb Dyementioning
confidence: 98%
“…Photocatalysis experiments were carried out with different sized (24,35 and 53 nm) ZTO nanoparticles (0.1 g in 100 ml of dye solution) and Methylene blue (MB) dye solution (10 ppm) in Millipore water. The photochemical reactor used in this study was made of a Pyrex glass jacketed quartz tube.…”
Section: Photocatalytic Degradation Of Mb Dye In Aqueous Solutionmentioning
confidence: 99%